Filsafat Analitik Bahasa dalam Perkembangan Ilmu Bahasa - Maulid Taembo; Tri Pujiati (Journal of Social, Culture, and Language, 2023)
Philosophy is the result of in-depth human thinking about reality and efforts to understand that reality which of course must be carried out according to certain rules. As for language is a sound system that is used to generate thoughts or feelings that can be studied based on a philosophical view. Analytic philosophy of language has an important role in language development, such as the emergence of new words, synonyms, acronyms, and more perfect grammatical structures. Language is not only seen as a means or medium of communication, but more than that language has its own identity which also discusses itself philosophically or based on philosophical studies which has a physical one in the form of language structures, writing forms, and language symbols. which bring the development of language. Key words: Language, language analytic philosophy, rules, and physical form